Faktor-faktor penentu stress dalam kalangan guru: Sekolah Rendah Mubaligh di Kuala Lumpur - Jumahat, Tajulashikin; Mohd Noor, Fazura; Ibrahim, Mohd Burhan (University of Malaya, 2013)
The purpose of this study was to identify the perceived level of stress based on demographic factors (gender, age, and teaching experience) and also to determine the contributing factors of stress among teachers who are currently teaching at Missionary Primary Schools in Kuala Lumpur. There are seven teacher’s stress sources that were included in this study which comprise workload, pupils’ attitude, time constraint, relationships with colleagues, relationships with parents, appreciation and support, and lack of resources. A total of 186 teachers from 14 Missionary Primary Schools in Kuala Lumpur were randomly chosen based on multistage cluster sampling that represents the total population. The data is analyzed by using both descriptive and inferential statistics (Independent t-test, one-way ANOVA test and Multiple Regression). The finding indicated that the stress level among respondents was at a moderate level. Further analysis revealed that there were no significant differences on the level of stress among respondents in terms of gender, age and work experience. In addition, it was found that parental relationship, and appreciation and support significantly predicted teacher’s stress level.